Effects of discretionary fiscal policy: New empirical evidence for Germany - Alexander Bank (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2011)
This paper analyses the effects of discretionary fiscal policy by presenting new empirical evidence for Germany within a structural vector autoregression (SVAR) framework. Following Blanchard and Perotti (2002), the SVAR model is identified by applying institutional information. We find no compelling evidence for the effectiveness of discretionary fiscal policy. Cutting taxes does not tend to stabilise the business cycle. Increasing government expenditure has an ambiguous effect on GDP for the basic specification. However, by controlling for the influence of inflation, higher government expenditure does not either tend to stabilise economic activity. The results are robust to various modifications.
Keywords: C32; E62; H30; 330; Discretionary fiscal policy; Germany; structural vector autoregression; Finanzpolitik; Diskretionäre Politik; Wirkungsanalyse; Konjunktur; Schätzung; Deutschland